Enhanced passive safety surveillance of a quadrivalent inactivated split virion influenza vaccine in Finland during the influenza season 2020/21 - Olga Syrkina; Ajinkya Inamdar; Sophie Wague; Céline Monfredo; Markku Nissilä; Anne-Laure Chabanon; Laurence Serradell (BMC Public Health, 2022)
Abstract Background The European Medicines Agency (EMA) requires enhanced safety surveillance to be conducted for annual seasonal influenza vaccines with the aim of rapidly detecting any potential new safety concerns before the peak immunisation period of the vaccine in any given year. The aim of this study was to detect any clinically significant change in the frequency or severity of expected reactogenicity of the quadrivalent inactivated split-virion influenza vaccine (IIV4) during routine immunisation in Finland for the 2020/21 season. The primary objective was to investigate the frequency of suspected adverse drug reactions (ADRs) occurring within 7 days following vaccination. Methods Enhanced passive safety surveillance of individuals vaccinated with IIV4 was conducted from October 9, 2020 to November 30, 2020 across seven sites in Finland. The vaccinee reporting rate and ADR reporting rate were calculated and compared with known or expected safety data in order to identify any clinically significant changes. Results Data were collected from 1008 individuals with 29 vaccinees reporting 82 suspected ADRs. Of these, 28 people reported 79 suspected ADRs within 7 days following vaccination, corresponding to a vaccinee reporting rate of 2.78% (95% CI: 1.85, 3.99) (ADR reporting rate, 7.84% [95% CI: 6.25, 9.67%]). The most frequently reported ADRs were injection site reactions (vaccination site pain, vaccination site erythema and vaccination site swelling) (n = 46, 2.28%), myalgia (n = 9, 0.89%) and headache (n = 8, 0.79%). No serious suspected adverse events were reported at any point post-vaccination and ADR reporting rates were in general lower compared to those reported for IIV4 in the 2019/20 surveillance study. Conclusion No clinically significant changes in what is known or expected for IIV4 were reported for the 2020/21 season which supports the safety profile of this vaccine and will help maintain public confidence in influenza vaccination.